A Comprehensive Update of Anti-COVID-19 Activity of Heterocyclic Compounds - Nazir MS; Ahmad M; Aslam S; Rafiq A; Al-Hussain SA; Zaki MEA (Dove Medical Press, 2024)
Muhammad Shahid Nazir,1 Matloob Ahmad,1 Sana Aslam,2 Ayesha Rafiq,1 Sami A Al-Hussain,3 Magdi EA Zaki3 1Department of Chemistry, Government College University, Faisalabad, Pakistan; 2Department of Chemistry, Government College Women University, Faisalabad, Pakistan; 3Department of Chemistry, Faculty of Science, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi ArabiaCorrespondence: Matloob Ahmad; Magdi EA Zaki, Email Matloob.Ahmad@gcuf.edu.pk; mezaki@imamu.edu.saAbstract: The Coronavirus disease 2019 (COVID-19) pandemic is one of the most considerable health problems across the world. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the major causative agent of COVID-19. The severe symptoms of this deadly disease include shortness of breath, fever, cough, loss of smell, and a broad spectrum of other health issues such as diarrhea, pneumonia, bronchitis, septic shock, and multiple organ failure. Currently, there are no medications available for coronavirus patients, except symptom-relieving drugs. Therefore, SARS-CoV-2 requires the development of effective drugs and specific treatments. Heterocycles are important constituents of more than 85% of the physiologically active pharmaceutical drugs on the market now. Several FDA-approved drugs have been reported including molnupiravir, remdesivir, ritonavir, oseltamivir, favipiravir, chloroquine, and hydroxychloroquine for the cure of COVID-19. In this study, we discuss potent anti-SARS-CoV-2 heterocyclic compounds that have been synthesized over the past few years. These compounds included; indole, piperidine, pyrazine, pyrimidine, pyrrole, piperazine, quinazoline, oxazole, quinoline, isoxazole, thiazole, quinoxaline, pyrazole, azafluorene, imidazole, thiadiazole, triazole, coumarin, chromene, and benzodioxole. Both in vitro and in silico studies were performed to determine the potential of these heterocyclic compounds in the fight against various SARS-CoV-2 proteins. Keywords: COVID-19, SARS-CoV-2, heterocyclic nucleus, in vitro, in silico, molecular docking studies